MEMBANGUN CITRA PERBANKAN SYARI’AH SEBUAH ALTERNATIF STRATEGI BAGI PENGEMBANGAN PERBANKAN SYARI’AH DI INDONESIA - Setiartiti, Lilies (Jurnal Ekonomi & Studi Pembangunan, 2004)
Meanwhile, the 1997 economic crisis and global economic down turn hard altogether becomes a trigger for the emergency of this new approach, as an alternative to interest-base economic system. In response to the growing demand and changing circumstances, the Government of the Republic of Indonesia then launched the unprecedented Sharia’s (or Islamic) Banking Enactment No. 7 in 1992, which initiated the legal framework for the dual banking system in the country. This initiation has fueled the establishment of the Islamic units as separate branches under conventional bank, following the pioneering full-fledge Islamic Banks. The growth of Islamic Banking and financial system brings about a new hope, that the new system would be able to lead millions of people to prosperity. However, it is not unchallenged. The first challenges stems from limited knowledge of the people about the Shari ‘ah Banking operation, limited number of bank, limited of number of bankers and management who possess sufficient understanding about Shari ‘ah